Epigenetics and sarcoidosis. (24th June 2021) - Konigsberg, Iain R.; Maier, Lisa A.; Yang, Ivana V.
Epigenetic modifications are emerging as important regulatory mechanisms of gene expression in lung disease, given that they are influenced by environmental exposures and genetic variants, and that they regulate immune and fibrotic processes. In this review, we introduce these concepts with a focus on the study of DNA methylation and histone modifications and discuss how they have been applied to lung disease, and how they can be applied to sarcoidosis. This information has implications for other exposure and immunologically mediated lung diseases, such as chronic beryllium disease, hypersensitivity pneumonitis, and asbestosis. In this review, we summarise recent findings relating to epigenetic modifications in lung disease with a focus on sarcoidosis, and propose guidelines and rationale for future epigenomic studies of sarcoidosis https://bit.ly/3d7Is1B